2017
DOI: 10.1371/journal.pmed.1002412
|View full text |Cite
|
Sign up to set email alerts
|

Impact of disinvestment from weekend allied health services across acute medical and surgical wards: 2 stepped-wedge cluster randomised controlled trials

Abstract: BackgroundDisinvestment (removal, reduction, or reallocation) of routinely provided health services can be difficult when there is little published evidence examining whether the services are effective or not. Evidence is required to understand if removing these services produces outcomes that are inferior to keeping such services in place. However, organisational imperatives, such as budget cuts, may force healthcare providers to disinvest from these services before the required evidence becomes available. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 35 publications
0
53
0
Order By: Relevance
“…Typically, reduced allied health services are available during weekends, with the goal of facilitating patient discharge, and preventing adverse events and escalation of care. Further, there is a variety in weekend allied health provision both within (22) and between health services (20,21). Within services, allied health departments have different levels of availability during weekends based on perceived benefits (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, reduced allied health services are available during weekends, with the goal of facilitating patient discharge, and preventing adverse events and escalation of care. Further, there is a variety in weekend allied health provision both within (22) and between health services (20,21). Within services, allied health departments have different levels of availability during weekends based on perceived benefits (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the AHA clinical role primarily involves providing therapy [7,32,40]. Given that previous evaluations on increasing allied health services in the acute setting have shown that its effects on patient and organisational outcomes are unclear, future evaluations on additional allied health services may consider the effects of increasing the ratio of AHA to allied health professional staffing [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…The mean hospital length of stay for relevant wards over the 1 month period preceding random group allocation, and the same corresponding month 12 months later. Hospital length of stay is a key driver of hospital efficiency [ 49 52 ] and provides a measure of benefit or non-inferiority for weekend allied health provision [ 37 , 38 , 53 ].…”
Section: Methodsmentioning
confidence: 99%